Handwriting Tics in Tourette’s Syndrome: A Single Center Study - Zanaboni Dina, Carlotta; Bona, Alberto R.; Zekaj, Edvin; Servello, Domenico; Porta, Mauro (Frontiers in Psychiatry, 2016)
Tourette’s syndrome (TS) is a neurodevelopmental disorder typically defined by multiple motor tics and at least one sound tic (1), beginning in childhood or in adolescence. More recently, Tourette’s syndrome has been acknowledged as a broad spectrum syndrome (2), including different comorbidities and coexisting symptoms. When beginning in early childhood TS mainly presents with attention deficit and hyperactivity disorder (ADHD) and tics, when beginning in adolescence instead tics and obsessive-compulsive behavior or disorder (OCB/OCD) are predominant. OCB/OCD trait is present in 60-80% of patients (3), and they are considered as thought tics (4). In many cases motor and sound tics resolve spontaneously in adulthood, though OCB/OCD generally remain. Tics often interfere with subject’s daily activities (5) affecting Quality of Life and causing Social Impairment, particularly in schooling and working. Handwriting is one of the most impaired school activity for TS patients because of the tics presence that hamper learning processes. In our clinical experience handwriting tics (HT) could severely affect and condition TS subjects, but they are not often pointed out in the Literature. For this reason there are not precise data regarding the incidence of HT neither in Tourette’s syndrome patients nor in healthy population.